2019
DOI: 10.1111/sms.13353
|View full text |Cite
|
Sign up to set email alerts
|

Does a bounding exercise program prevent hamstring injuries in adult male soccer players? – A cluster‐RCT

Abstract: BackgroundAlthough the Nordic Hamstring Exercise (NHE) prevents hamstring injury in soccer players effectively, the annual incidence of these injuries still increases. This may be because of poor long‐term compliance with the program. Furthermore, the timing and amplitude of gluteal and core muscle activation seem to play an important role in hamstring injury prevention, the NHE program was not designed to improve activation of these muscles. Therefore, we propose plyometric training as an alternative to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…These observations, regarding low compliance, could likely explain the continuous rise in hamstring strain injuries in elite football 14 21 52. We also found moderate quality of evidence for a trivial non-significant effect of a comprehensive bounding programme involving plyometric and running drills directed towards the injury mechanisms during high-speed running 63…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…These observations, regarding low compliance, could likely explain the continuous rise in hamstring strain injuries in elite football 14 21 52. We also found moderate quality of evidence for a trivial non-significant effect of a comprehensive bounding programme involving plyometric and running drills directed towards the injury mechanisms during high-speed running 63…”
Section: Discussionmentioning
confidence: 66%
“…Based on this, the Nordic hamstring exercise protocol showed a large and significant risk reduction (RR: 0.35, 95% CI 0.22 to 0.54; I 2 =0.0%) compared with usual care on hamstring injuries in football (n=1521) (high quality of evidence) 56 57. Data from individual studies62–65 are presented in table 2.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This study reported no statistically significant differences in hamstring injury incidence (odds ratio = 0.89 [95% CI 0.46, 1.75]) or severity between the groups. 40…”
Section: Eccentric Trainingmentioning
confidence: 99%
“…The video component of this article can be found at https://www.jove.com/video/60857/ 14,15,16,17 . Furthermore, the number of athletes that sustain a hamstring strain injury rises each year 18,19 , despite that multiple programs have been introduced to prevent hamstring strain injuries 12,13,20,21…”
Section: Video Linkmentioning
confidence: 99%